2013
DOI: 10.1039/c3ib40166a
|View full text |Cite
|
Sign up to set email alerts
|

Postulates on electromagnetic activity in biological systems and cancer

Abstract: A framework of postulates is formulated to define the existence, nature, and function of a coherent state far from thermodynamic equilibrium in biological systems as an essential condition for the existence of life. This state is excited and sustained by energy supply. Mitochondria producing small packets of energy in the form of adenosine and guanosine triphosphate and strong static electric field around them form boundary elements between biochemical-genetic and physical processes. The transformation mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…It is now also thought that photosynthesis utilises fundamental quantum principles, involving coherence and excitons to transfer energy efficiently [38,39,41] This is especially interesting as lysozyme appears to demonstrate a Fröhlich condensate; Fröhlich suggested that terahertz radiation could be absorbed by proteins leading to them behaving as a series of coupled oscillators generating a macroscopic quantum effect [49]. If combined with the concept that the electro-magnetic (EM) fields generated by mitochondria can lead to water order, this suggests an overall protection against decoherence within the cell [50]. Indeed, it has been suggested that quantum coherence can be maintained for significant periods of time in complex biological systems as they can hover in a poised realm between the pure quantum and incoherent classical worlds [51].…”
Section: The Emergence Of Quantum Biologymentioning
confidence: 99%
“…It is now also thought that photosynthesis utilises fundamental quantum principles, involving coherence and excitons to transfer energy efficiently [38,39,41] This is especially interesting as lysozyme appears to demonstrate a Fröhlich condensate; Fröhlich suggested that terahertz radiation could be absorbed by proteins leading to them behaving as a series of coupled oscillators generating a macroscopic quantum effect [49]. If combined with the concept that the electro-magnetic (EM) fields generated by mitochondria can lead to water order, this suggests an overall protection against decoherence within the cell [50]. Indeed, it has been suggested that quantum coherence can be maintained for significant periods of time in complex biological systems as they can hover in a poised realm between the pure quantum and incoherent classical worlds [51].…”
Section: The Emergence Of Quantum Biologymentioning
confidence: 99%
“…A great deal of energy is released from mitochondria during the respiration processes. Some authors suggest that a part of the "wasted" energy flux released from mitochondria could power the vibration modes of microtubules [44]. Endogenous nonthermal chemical electronic excitations take place in biological systems [2].…”
Section: Further Open Questionsmentioning
confidence: 99%
“…Long-lasting interaction consequences of ELF EMF can be evaluated under three main headings as cancer cases, cardiac results and diabetes according to experimental and epidemiological studies [26][27][28][29].…”
Section: Journal Of Biochemistry and Biophysicsmentioning
confidence: 99%